Population Pharmacokinetics and Monte Carlo Simulation for Dosage Optimization of Fosfomycin in the Treatment of Osteoarticular Infections in Patients without Renal Dysfunction - Rinaldi, Matteo (Antimicrob Agents Chemother, 2021)
Fosfomycin is gaining interest in the treatment of complex osteoarticular infections (OI) due to multidrug-resistant (MDR) pathogens. Our aims were to conduct population pharmacokinetics of fosfomycin in a cohort of OI patients receiving 16 g daily by intermittent (II) or continuous (CI) infusion and to carry out Monte Carlo simulations for dosage optimization in the treatment of these infections. Patients underwent blood sampling on day 5 of therapy (2 to 3 serial samples). Population pharmacokinetics and Monte Carlo simulations were performed to define the probability of target attainment (PTA) of 70% T>MIC and the cumulative fraction of response (CFR) against common OI pathogens with dosages of 8, 12, 16, and 20 g/day administered by II, extended infusion (EI), or CI. Forty-eight patients were recruited. A two-compartment open model with infusion input and first-order elimination was developed. Estimated creatinine clearance (CL(CR)) was included as a covariate in the final model. Monte Carlo simulations showed that optimal PTAs and CFRs (≥90%) can be achieved in three different classes of renal function by administering a daily dosage of 2 g every 6 h (q6h) by II against Staphylococcus aureus, Escherichia coli, expanded-spectrum beta-lactamase (ESBL)-producing E. coli, and methicillin-resistant S. aureus; 8 g by CI against coagulase-negative staphylococci, K. pneumoniae, and ESBL-producing K. pneumoniae; 12 g by CI against P. aeruginosa; and 16 g by CI against KPC-producing K. pneumoniae. Our study provides a strong rationale for considering fosfomycin dosages of 8 to 16 g daily by CI in several clinical scenarios for OI patients. The feasibility of administration by CI in an elastomeric pump makes fosfomycin a candidate for OPAT programs.